On a global classical solution of a quasilinear hyperbolic equation - Y. Ebihara; D. C. Pereira (International Journal of Mathematics and Mathematical Sciences)
In this paper we establish the existence and uniqueness of global classical solutions for the equation which arises in the study of the extensional vibrations of thin rod, or torsional vibrations of thin rod.